PRIMARY SCHOOL EDUCATION LEVEL EVALUATION OF THE WEDNESDAY READING MOVEMENT (GERABA) PROGRAMME - Aula Nurussalamah, Nisa (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
This study aims to analyze the implementation of the GERABA (Wednesday Reading Movement) program, supporting factors as well as inhibiting factors and input as improvements to the program. This type of research uses descriptive qualitative by applying the Context, Input, Process and Product (CIPP) evaluation model. The subjects in this study were school principals and teachers who were involved in implementing the Wednesday Reading Movement (GERABA) program at Sarakan 2 Public Elementary School. Data were collected by means of observation, interviews, and document study. The results of the context research analysis show that the implementation of the GERABA program at SD Negeri Sarakan 2 which is carried out routinely every Wednesday has not been able to increase students' interest in reading, while the input by the facilities and infrastructure is considered inadequate. In the process component which includes retelling up to the library visit it is still difficult to do, and in the product component the expected output has not been optimally achieved.